ANALISIS NILAI-NILAI KARAKTER SISWA PADA PEMBELAJARAN EKONOMI DI SMA NEGERI 2 TANJUNG RAJA - Abdul Hamid; Riswan Jaenudin; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This study aims to know the character values of the students in economic learning at SMAN 2 Tanjung Raja. The method in this study is descriptive.Subjectsin this study are 51 students from class X IPS 2 and XI IPS 3. The technique of data collection used questionnaire and interview as the primary method, observation and documentation as the secondary method. The result of this study showed character values of the students in economic learning at SMAN 2 Tanjung Raja that high category with the average score of 3.7. There are five character values developed through learning by economic teacher. Character honest students showed the average score of 3.7 which classified in high category. Character discipline students showed the average score of 3.7 which classified in high category. Character curiosity of students showed the average score of 4.0 which classified in high category. Character social care students showed the average score of 3.6 which classified in high category. Character responsibility of students showed the average score of 3.6 which classified in high category. Furthermore, they find a way of teachers in developing the character values of students through the economic learning at SMAN 2 Tanjung Raja by putting motivational words in examination sheet like honesty is more valuable than the value without the honesty, the consequences of giving extra score and stars when the students obeying rules and giving punishment separate study of friends if they break the rules, active learning model, ice breaking, visiting sick friends, and spritual cleansing.